GREEN TECHNOLOGY INNOVATION & KINERJA KEUANGAN PERUSAHAAN: MEDIASI KINERJA LINGKUNGAN: - - Sari, Puspita (Universitas Airlangga, 2024)
The study aims to prove empirically that environmental performance mediates the effect of green technology innovation on corporate financial performance. This study uses SEM-PLS to analyze data and Warpl PLS 7.0 software to process the data. This study uses a purposive sampling method with many samples of 180 companies in the basic industrial sector and chemicals, mining, and agriculture listed on the Indonesia Stock Exchange and PROPER Indonesia rating during 2013-2018. The result shows that environmental performance partially mediates the effect of green product innovation on corporate financial performance which measured by ROA and ROE. Environmental performance was also found to be inconsistent mediates the effect of green process innovation on corporate financial performances which measured by ROA. The results of this study have confirmed the Resource Based View Theory and Natural Resource Based View Theory.